Proceedings of the 6th International Conference on Security of Information and Networks 2013
DOI: 10.1145/2523514.2527022
|View full text |Cite
|
Sign up to set email alerts
|

Preventing malicious data harvesting from deallocated memory areas

Abstract: The possibility of unauthorized data exposure caused by memory deallocation flaws in various software products has been accentuated by some IT-security experts several years ago [1,2,3,4]. However, no feasible and universal strategies have been proposed so far to reduce that risk. In this paper we discuss possible approaches to reducing the chances of undesirable exposure of sensible information caused by unreasonably long data lifetime in main memory. We offer several directions of how current development pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…This extension to Android encrypts sensitive data objects in place, and then when the object is no longer needed or it's idle, the key is securely deallocated. However, when considering server-side changes, re-engineering the JVM should also consider dealing with sensitive native IO operations, shared variables in applications [8], and incorporating explicit data lifetimes into the programming language [7,9].…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…This extension to Android encrypts sensitive data objects in place, and then when the object is no longer needed or it's idle, the key is securely deallocated. However, when considering server-side changes, re-engineering the JVM should also consider dealing with sensitive native IO operations, shared variables in applications [8], and incorporating explicit data lifetimes into the programming language [7,9].…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…However, Chow et al's techniques cannot address the latent secrets found in the HotSpot, because the JVM uses it's own memory management primitives. Additional work has been done to help reduce latent secrets due to shared program variables with static analysis [8]; Anikeev et al [9] proposed introducing keywords into managed languages hinting at how to securely manage object instances.…”
Section: Prior Workmentioning
confidence: 99%
“…CODIC can also be used to accelerate secure deallocation mechanisms [10,34,45,59,140]. Secure deallocation is a technique that sets the data to zero at the moment of deallocation, or as soon as the data is not needed anymore, which reduces the time that critical data is exposed to attacks.…”
Section: Other Applicationsmentioning
confidence: 99%
“…We conclude that our zero-runtime-overhead proposal is a very power-and areaefficient way to protect against cold boot attacks in systems where encryption is expensive or otherwise undesirable. 10…”
Section: Comparison With Other State-of-the-art Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation